2021
DOI: 10.3389/fpsyg.2021.716485
|View full text |Cite
|
Sign up to set email alerts
|

A Challenge for Contrastive L1/L2 Corpus Studies: Large Inter- and Intra-Individual Variation Across Morphological, but Not Global Syntactic Categories in Task-Based Corpus Data of a Homogeneous L1 German Group

Abstract: In this paper, we present corpus data that questions the concept of native speaker homogeneity as it is presumed in many studies using native speakers (L1) as a control group for learner data (L2), especially in corpus contexts. Usage-based research on second and foreign language acquisition often investigates quantitative differences between learners, and usually a group of native speakers serves as a control group, but often without elaborating on differences within this group to the same extent. We examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 108 publications
0
5
1
Order By: Relevance
“…
Research on multilingual speakers is often compared to monolingual baselines which are commonly treated as if they were homogeneous across speakers. Despite recent research showing that this homogeneity does not hold (Shadrova et al, 2021), this reproduces native-speakerism and monolingualism. Heritage language research, which established itself in the past two decades, is no exemption.
…”
contrasting
confidence: 69%
See 1 more Smart Citation
“…
Research on multilingual speakers is often compared to monolingual baselines which are commonly treated as if they were homogeneous across speakers. Despite recent research showing that this homogeneity does not hold (Shadrova et al, 2021), this reproduces native-speakerism and monolingualism. Heritage language research, which established itself in the past two decades, is no exemption.
…”
contrasting
confidence: 69%
“…Much recent research shows that this homogeneity does not hold (Castro et al, 2022;May, 2020;Shadrova et al, 2021). Depending on the linguistic phenomenon under investigation, these studies show that there is large variation between producers, and even within a single producer there is variation depending on vastly different communicative situations.…”
Section: Introductionmentioning
confidence: 96%
“…This was the start of an ongoing push to rethink the idea of the native speaker, and a lot of literature has discussed alternative approaches (e.g., Bayram et al, 2019; Rothman & Treffers-Daller, 2014). Fundamentally, much recent research shows that the assumed homogeneity does not hold (Castro et al, 2022; May, 2020; Shadrova et al, 2021; Shin, 2022). More specifically, Shadrova et al (2021) investigated narrative production data in a well-controlled corpus of German native speakers which is often used for comparisons with L2 learners.…”
Section: Introductionmentioning
confidence: 99%
“…Research findings show that different-level learners prefer using different lexical and syntactic structures in their written work, with beginners using high-frequency vocabulary, parallel structures, and simple sentences, intermediate learners tending to use low-frequency vocabulary and subordinate clauses, and advanced learners often using simple language structures (e.g., noun phrases) to express more complex ideas (Ortega, 2003;Vyatkina, 2013). Similarly, recent studies have found that there are significant differences in specific syntactic indicators between L2 learners and native speakers, with bilingual learners tending to use more parallel structures and native speakers tending to use more subordinate and complex phrase structures (Bulté and Housen, 2014;Mancilla et al, 2017;Shadrova et al, 2021). Notwithstanding difference in learners' level of syntactic development, high-quality compositions shared similar linguistic features, such as the use of more complex sentences and diverse phrase structures, as well as low-frequency vocabulary to convey meaning (McNamara et al, 2010).…”
Section: Empirical Research On the Effect Of Learning Context On L2 W...mentioning
confidence: 99%